Fiqh Learning with Demonstration Method to Form Student Character MA Muhammadiyah 11 Memorization of the Qur'an Kranji - Ain, Qurrotul; Tobrani, Tobrani; Humaidi, M Nurul (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
This study aims to describeFiqh learning at MAM 11 Tahfidul Qur'an Kranji, implementation of demonstration method in fiqh learning to shape students' character at MAM 11 Tahfidul Qur'an Kranji and the impact of fiqh learning with demonstration method to shape students' character at MAM 11 Tahfidul Qur'an Kranji. The approach used in this research is a qualitative approach, namely describing and outlining learning using demonstration methods in forming student character.with data collection techniques including participant observation of the learning process, in-depth interviews with Fiqh teachers and students, and analysis of documentation related to learning planning and implementation. The research subjects were students of MA Muhammadiyah 11 Tahfidzul Qur'an. The research findings show that the implementation of the demonstration method in Fiqh learning provides a significant contribution to the formation of student character, especially in aspects of discipline, accuracy, responsibility, cooperation, empathy, and submission in worship. Educators as demonstrators also play a role as role models in displaying Islamic characters.